Finding Care in Networked Learning: close encounter with a virtual assistant - Cutajar, Maria (Proceedings of the International Conference on Networked Learning, 2026)
A theme that emerged from the selection of papers drawn from the 14th edition of the networked learning conference and included in the edited book in the Research in Networked Learning series was that of care. The editorial team noted that while care is an assumed aspect of networked learning, it has not received direct attention in the networked learning literature. What began as a curiosity about the presence of care in recent networked learning scholarship developed into a motivated inquiry to examine both the thematic representation of care and the possibilities researching with a virtual assistant. The guiding question was: What are the distinct ways in which care is thematically represented in recent networked learning literature? The question was answered with reference to the proceedings of the two most recent conferences on networked learning that generated a dataset of 92 papers. This corpus was chosen as representative of the field in the period following the Covid-19 pandemic and the concurrent rise of generative artificial intelligence (Gen-AI) and other AI-driven applications. These developments and related regulatory debates increased the attention to care and care ethics. The study confirms the limited direct focus on care in the recent networked learning publications. From the small subset of papers that explicitly address the theme, it is evident that care in technology mediated education settings is a troubling concern, spanning practices, approaches, values and beliefs and tensions in the intersectionalities cutting across them. Care demands genuine action towards the mattering of both human and non-human actors. The tensions surfaced suggest that care needs to be foregrounded more explicitly in networked learning to highlight conflicting perspectives, counter hollow political discourse, and emphasise care as integral to design, implementation and practice. As the postdigital entanglement with sophisticated AI-driven technologies deepens, appeals for care and care ethics are expected to intensify. This experimental study conducted with a chatbot illustrates such entanglement. The personal experience of doing this work further underscores the necessity of human oversight – not only to verify and validate the outputs of non-caring algorithmic systems but also to ensure that digital assistants remain accountable tools rather that arbiters of what the world is.